Development of Pedestrian Level of Service (PLOS) for Jaywalking Pedestrians at Unsignalised Intersections on Urban Arterials Using Ann &Amp; Clustering: A Case Study in India - Ampereza Ankunda; Malaya Mohanty; Satya Ranjan Samal (Communications)
In a developing country like India where jaywalking is prevalent than using designated crosswalks, pedestrian safety is a major concern. Development of pedestrian level of service (PLOS) is essential for monitoring pedestrian safety for these manoeuvres. The present research incorporates a new methodology to evaluate pedestrian LOS for jaywalkers. The study is conducted in a smart city of Bhubaneswar in India. The pedestrian crossing speeds ranged from 0.6 to 1.4 m/s. Artificial Neural Networks (ANN) are used to determine the pedestrian crossing speeds from vehicular and pedestrian counts whose outputs are close to the field data. A 2-step K-means clustering technique is employed to determine the Pedestrian LOS ranges based on pedestrian crossing speeds. Urban planners, transportation engineers, and legislators can use the methodology to determine PLOS levels to create the pedestrian-friendly infrastructure.